Theologie für die Praxis | 49. Jg. (2023): Christentum und Judentum - Im Auftrag der Theologischen Hochschule Reutlingen; Barthel, Jörg; Bühler, Maximilian; Schluep, Christoph; Voigt, Christof (Evangelische Verlagsanstalt, 2024)
Two previously unpublished drafts on eschatology are published in this volume: a lecture by the Zurich fundamental theologian Walter Mostert and a series of theses by the Tübingen systematist Eberhard Jüngel. They are supplemented by other texts by the two well-known authors, which also deal with eschatological topics. In contrast to current apocalyptic slogans and actions that conjure up the end of the world and the end of time, but also in the critical contrast to a desolate silence in the face of the power of death, a biblically based Reformation eschatology is discussed here that is extremely current and therefore deserves to be widely recognized.